2011
DOI: 10.3389/fnbeh.2011.00052
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Memory Recall and Talkativeness for Emotional Stimuli

Abstract: Recent studies have evidenced an increasing interest in sex-related brain mechanisms and cerebral lateralization subserving emotional memory, language processing, and conversational behavior. We used event-related-potentials (ERP) to examine the influence of sex and hemisphere on brain responses to emotional stimuli. Given that the P300 component of ERP is considered a cognitive neuroelectric phenomenon, we compared left and right hemisphere P300 responses to emotional stimuli in men and women. As indexed by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 94 publications
2
12
0
Order By: Relevance
“…A set of slides was accompanied by a simple narrative, either a neutral version or an arousing one. In addition to their previous ERP finding, they also found that men, not women, recalled the arousing story better than the neutral version (Arnone, Pompili, Tavares, & Gasbarri, 2011).…”
Section: Hemispheric Lateralization In Affective Neurosciencesupporting
confidence: 52%
“…A set of slides was accompanied by a simple narrative, either a neutral version or an arousing one. In addition to their previous ERP finding, they also found that men, not women, recalled the arousing story better than the neutral version (Arnone, Pompili, Tavares, & Gasbarri, 2011).…”
Section: Hemispheric Lateralization In Affective Neurosciencesupporting
confidence: 52%
“…Indeed, different studies reviewed used only females (e.g., Tomarken et al, 1990 ; Wheeler et al, 1993 ; Gotlib et al, 1998 ; Reid et al, 1998 ; Gale et al, 2001 ), or much more females than males (e.g., Dennis and Solomon, 2010 ; Mikolajczak et al, 2010 ); one study enrolled only males (Jacobs and Snyder, 1996 ), and one study reported no information about gender (Warden-Smith et al, 2017 ). Only recently studies have increased the interest in gender-related brain mechanisms and cerebral lateralization subserving emotional processing (e.g., Gasbarri et al, 2006 , 2007 ; Arnone et al, 2011 ). In particular, unpleasant stimuli (negatively valenced IAPS pictures) were found to elicit higher P300 amplitude and shorter P300 latency at left frontal site than pleasant and neutral stimuli in women than in men, while a stronger P300 component was elicited in the right hemisphere in men compared to women (e.g., Gasbarri et al, 2007 ; Arnone et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only recently studies have increased the interest in gender-related brain mechanisms and cerebral lateralization subserving emotional processing (e.g., Gasbarri et al, 2006 , 2007 ; Arnone et al, 2011 ). In particular, unpleasant stimuli (negatively valenced IAPS pictures) were found to elicit higher P300 amplitude and shorter P300 latency at left frontal site than pleasant and neutral stimuli in women than in men, while a stronger P300 component was elicited in the right hemisphere in men compared to women (e.g., Gasbarri et al, 2007 ; Arnone et al, 2011 ). In addition, participants' age might also be another confounding factor because different wide age ranges are reported across studies, even including over 50 (e.g., Jacobs and Snyder, 1996 ; Dennis and Solomon, 2010 ) or 60-year people (e.g., Hall and Petruzzello, 1999 ; Mathersul et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of emotion on memory has been abundantly demonstrated using various types of materials, including emotional stories (Gasbarri et al, 2005; Nielsen et al, 2013), pictures (Pompili et al, 2016), and words (Arnone et al, 2011). However, images of emotional faces differ from other arousing pictures or words because of their affective value (Calvo and Nummenmaa, 2016).…”
Section: Introductionmentioning
confidence: 99%